MOTIF AND MEANING OF HIJRAH FOR PUNK MEMBERS OF THE UNDERGROUND TASAWUF COMMUNITY - Ade Irfan Abdurahman; Faisal Tomi Saputra; Muhammad Kevin Rahmaddan; Randi Febriary (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2023)
This research is motivated by the phenomenon of hijrah in marginal communities, especially the underground Sufism community. This community is very concerned about the fate of Punk children around Jabodetabek. On this basis, the researcher was moved to conduct research on the meaning of 'hijrah' for the Punk children of the Underground Tasawuf Community. This research uses the phenomenological method in examining the theme of this discussion. The results of this study indicate that there are two motives for hijrah, first; awareness for wrong behavior and family motives. Meanwhile, hijrah means moving to the sea of ​​knowledge, changing attitudes and improving the quality of worship, cleaning up from heart disease, forgiving and being devoted to parents.